Polyamines, myosin heavy chains, and collagen specific amino acids after a repeated bout of eccentric exercise. Issue 3 (2nd July 2016) - Behringer, Michael; Montag, Johannes Caspar Konrad; Kilian, Yvonne; Heaton, Phil; Mester, Joachim
ABSTRACT: We investigated alternatives to commonly used biomarkers of exercise-induced tissue damage. Over 5 days following two bouts of 100 drop-to-vertical jumps (inter-bout rest period of 3 weeks), myosin heavy chain 1, hydroxylysine (HYL), hydroxyproline (HYP), spermine (SPM) and spermine synthase (SMS) were measured in the serum of 10 participants. HYL significantly increased from 5.92 ± 1.49 ng/mL to 6.48 ± 1.47 ng/mL at 24 h. A similar trend was observed for bout 2, but without reaching significance. SPM significantly increased only after bout 1 from 0.96 ± 0.19 ng/mL at pretest to a peak level of 1.12 ± 0.26 ng/mL at 24 h, while B2 increments remained non-significant. Myosin heavy chain 1, HYP and SMS values remained below the detection limit of the applied enzyme-linked immunosorbent assay (ELISA) kit. Though HYL and SM increased after the intervention, both markers showed a large standard deviation (SD) combined with small increments. Therefore, none of the investigated biomarkers provides a meaningful alternative to commonly used damage markers.